Lithium iron phosphate positive electrode material and preparation method thereof
Patent Information
- Application Number
- CN202611407349.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]鉴于此,本发明提供一种磷酸铁锂正极材料及其制备方法,旨在通过预锂化处理对磷酸铁进行晶格活化,以解决现有技术中锂化反应不充分、晶粒异常长大及压实密度偏低的问题,同时提升材料的电化学性能和循环稳定性
本发明通过控制预锂化阶段第一锂源的添加比例和预锂化温度,使无水磷酸铁发生部分锂化,锂离子嵌入磷酸铁晶格中,有效改变其晶格结构和表面状态,增加反应活性位点,使后续高温烧结过程中碳热还原反应和锂化反应更加充分,有助于生成晶相纯度高、缺陷少的磷酸铁锂产物。同时,预锂化处理所得中间相组成相对可控,避免了高温预烧时中间相组成复杂难以调控的问题,从而提升材料的放电比容量和循环稳定性,实现压实性能与电化学性能的优化。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery cathode material technology, specifically to a lithium iron phosphate cathode material and its preparation method. Background Technology
[0002] Lithium iron phosphate (LiFePO4) cathode materials have become one of the mainstream cathode materials in the fields of power batteries and energy storage batteries due to their excellent thermal stability, good cycle life, abundant raw material sources, and low cost. With the continuous improvement of the driving range of new energy vehicles and the increasing demands for volumetric energy density in energy storage systems, the market has placed higher requirements on the compaction density and electrochemical performance of lithium iron phosphate cathode materials. High-compact lithium iron phosphate can fill more active material in the same volume, thereby increasing the volumetric energy density of the battery cell.
[0003] In the preparation of lithium iron phosphate (LFP), the solid-state reaction between the iron phosphate precursor and the lithium source is the core step. Traditional methods typically involve mixing iron phosphate, the lithium source, the carbon source, and dopants in a single step followed by high-temperature sintering. However, this process suffers from insufficient reactivity between the iron phosphate and lithium source during sintering, leading to incomplete lithiation or uneven lithium concentration in certain areas, thus affecting the phase purity and electrochemical performance of the material. Furthermore, abnormal grain growth is common during high-temperature sintering, resulting in uneven particle distribution and impacting compaction density. In addition, conventional one-step sintering methods struggle to effectively control the formation and transformation of the intermediate phase, resulting in a relatively simple solid-state reaction pathway and numerous lattice defects in the product, limiting the material's application in high-compact and high-rate magnification scenarios. Summary of the Invention
[0004] In view of this, the present invention provides a lithium iron phosphate cathode material and its preparation method, which aims to activate the lattice of iron phosphate through pre-lithiation treatment to solve the problems of insufficient lithiation reaction, abnormal grain growth and low compaction density in the prior art, while improving the electrochemical performance and cycle stability of the material.
[0005] The technical solution provided by this invention is as follows: In a first aspect, the present invention provides a method for preparing a lithium iron phosphate cathode material, comprising the following steps: (1) Anhydrous iron phosphate is mixed with the first lithium source and pre-lithiation is carried out at 430~530℃ under an inert atmosphere to obtain the pre-lithiation product; (2) The pre-lithiation product, the second lithium source, the carbon source, and the dopant are added to a solvent and mixed and dispersed to obtain a slurry; (3) Grind the slurry and spray dry it to obtain precursor powder; (4) The precursor powder is sintered at 720~800℃ under an inert atmosphere; (5) The sintered product is crushed, sieved and demagnetized to obtain lithium iron phosphate cathode material.
[0006] Furthermore, in step (1), the first lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; the molar ratio of iron in anhydrous iron phosphate to lithium in the first lithium source is 1:(0.60~0.85); and the pre-lithiation treatment time is 2~8h.
[0007] Furthermore, in step (2), the second lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; the amount of the second lithium source added is such that the molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is (1.00~1.05):1.
[0008] Furthermore, in step (2), the carbon source is selected from at least one of glucose, sucrose, starch, citric acid, polyethylene glycol, and polyvinyl alcohol; the amount of carbon source added is 5 to 18% of the mass of anhydrous ferric phosphate.
[0009] Furthermore, in step (2), the dopant is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium tetrachloride, ammonium metavanadate, and magnesium oxide; the amount of dopant added is 0.05~1.5% of the mass of the anhydrous iron phosphate.
[0010] Furthermore, in step (2), the solvent is deionized water.
[0011] Furthermore, the solid content of the slurry in step (2) is 40~70wt%.
[0012] Furthermore, the sintering time in step (4) is 4~12h.
[0013] Furthermore, the inert atmosphere in steps (1) and (4) is nitrogen or argon.
[0014] Secondly, the present invention provides a lithium iron phosphate cathode material, which is prepared by a method for preparing a lithium iron phosphate cathode material as described in any of the preceding claims.
[0015] Thirdly, the present invention provides the application of the lithium iron phosphate cathode material as described above in lithium batteries.
[0016] The beneficial effects of this invention are as follows: This invention achieves partial lithiation of anhydrous iron phosphate by controlling the addition ratio of the first lithium source and the pre-lithiation temperature during the pre-lithiation stage. Lithium ions are embedded in the iron phosphate lattice, effectively altering its crystal structure and surface state, increasing reactive sites, and allowing for more complete carbothermic reduction and lithiation reactions during subsequent high-temperature sintering. This contributes to the generation of lithium iron phosphate products with high crystal purity and few defects. Simultaneously, the composition of the intermediate phase obtained from the pre-lithiation treatment is relatively controllable, avoiding the problem of complex and difficult-to-control intermediate phase composition during high-temperature pre-sintering. This improves the material's discharge specific capacity and cycle stability, optimizing compaction and electrochemical performance. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only a part of the embodiments of this invention, not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and parts by weight.
[0018] Unless otherwise specified, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. It should be noted that the terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the exemplary embodiments of this application.
[0019] The technical solution of this invention is: a method for preparing lithium iron phosphate cathode material, comprising the following steps: (1) Anhydrous iron phosphate and the first lithium source are mixed at a molar ratio of Li to Fe of (0.60~0.85):1, and placed in a sintering furnace under nitrogen or argon atmosphere protection. The mixture is pre-lithiated at a temperature of 430~530℃ for 2~8h to obtain the pre-lithiated product. (2) The pre-lithiation product is mixed and dispersed with the second lithium source, carbon source and dopant in deionized water, wherein the amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is (1.00~1.05):1, the amount of carbon source added is 5~18% of the mass of anhydrous iron phosphate, and the amount of dopant added is 0.05~1.5% of the mass of anhydrous iron phosphate, and a slurry with a solid content of 40~70wt% is prepared. (3) The slurry is put into a sand mill for grinding, and then spray dried to obtain precursor powder; (4) Place the precursor powder in a sintering furnace under nitrogen or argon atmosphere protection and sinter at a temperature of 720~800℃ for 4~12h. (5) The sintered material is subjected to air jet milling, sieve through a 300-mesh screen and demagnetization treatment to obtain lithium iron phosphate cathode material; The first lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate. The second lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; The carbon source is selected from at least one of glucose, sucrose, starch, citric acid, polyethylene glycol, and polyvinyl alcohol; The dopant is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium tetrachloride, ammonium metavanadate, and magnesium oxide.
[0020] In this invention, by controlling the amount of the first lithium source added during the pre-lithiation stage, anhydrous iron phosphate is partially lithiated, and lithium ions are embedded in the iron phosphate lattice to form a pre-lithiated product with an activated lattice structure. This pre-lithiation treatment can effectively change the lattice structure and surface state of anhydrous iron phosphate, increase the reactive sites, and make the lithiation reaction more complete and uniform during the subsequent high-temperature sintering process. Example
[0021] This embodiment provides a method for preparing lithium iron phosphate cathode material, including the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.75:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 480°C for 5 hours to obtain the pre-lithiated product. (2) The pre-lithiation product, lithium carbonate (second lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, so as to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material. Example
[0022] This embodiment provides a method for preparing lithium iron phosphate cathode material, including the following steps: (1) Anhydrous iron phosphate and lithium hydroxide (first lithium source) were mixed at a molar ratio of Li to Fe of 0.70:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 460°C for 6 hours to obtain the pre-lithiated product. (2) The pre-lithiation product is mixed and dispersed with lithium hydroxide (second lithium source), sucrose (carbon source) and ammonium metavanadate (dopant) in deionized water. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.03:1. The amount of sucrose added is 12% of the mass of anhydrous iron phosphate, and the amount of ammonium metavanadate added is 0.5% of the mass of anhydrous iron phosphate. A slurry with a solid content of 60wt% is prepared. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.6μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 780°C for 6 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material. Example
[0023] This embodiment provides a method for preparing lithium iron phosphate cathode material, including the following steps: (1) Anhydrous iron phosphate and lithium oxalate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.80:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 500°C for 4 hours to obtain the pre-lithiated product. (2) The pre-lithiation product is mixed and dispersed with lithium carbonate (second lithium source), starch (carbon source) and tetrabutyl titanate (dopant) in deionized water. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.03:1. The amount of starch added is 8% of the mass of anhydrous iron phosphate, and the amount of tetrabutyl titanate added is 1.0% of the mass of anhydrous iron phosphate. A slurry with a solid content of 50wt% is prepared. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.8μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 740°C for 10 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0024] Comparative Example 1 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate, lithium carbonate (lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed, wherein the molar ratio of lithium to iron is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, and a slurry with a solid content of 55wt% is prepared. (2) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (3) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (4) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0025] The difference between this comparative example and Example 1 is that: no pre-lithiation treatment is performed, and anhydrous iron phosphate is directly mixed with all lithium sources, carbon sources and dopants and then sintered in one step.
[0026] Comparative Example 2 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.30:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 480°C for 5 hours to obtain the pre-lithiated product. (2) The pre-lithiation product, lithium carbonate (second lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, so as to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0027] The difference between this comparative example and Example 1 is that the molar ratio of Li to Fe in the pre-lithiation treatment in step (1) is 0.30:1, while the rest are the same as in Example 1.
[0028] Comparative Example 3 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.95:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 480°C for 5 hours to obtain the pre-lithiated product. (2) The pre-lithiation product, lithium carbonate (second lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, so as to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0029] The difference between this comparative example and Example 1 is that the molar ratio of Li to Fe in the pre-lithiation treatment in step (1) is 0.95:1, while the rest are the same as in Example 1.
[0030] Comparative Example 4 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.75:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 600°C for 5 hours to obtain the pre-lithiated product. (2) The pre-lithiation product, lithium carbonate (second lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, so as to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0031] The difference between this comparative example and Example 1 is that the temperature of the pre-lithiation treatment in step (1) is 600°C, while the rest are the same as in Example 1.
[0032] Comparative Example 5 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.75:1 and placed in a sintering furnace under nitrogen atmosphere protection. The mixture was pre-lithiated at 480°C for 5 hours to obtain the pre-lithiated product. (2) The pre-lithiation product, lithium carbonate (second lithium source), glucose (carbon source) and titanium dioxide (dopant) are added to deionized water and mixed and dispersed. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, the amount of glucose added is 10% of the mass of anhydrous iron phosphate, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, so as to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) Place the precursor powder in a sintering furnace under nitrogen atmosphere protection and sinter at 900°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0033] The difference between this comparative example and Example 1 is that the sintering temperature in step (4) is 900℃, while the rest are the same as in Example 1.
[0034] Comparative Example 6 A method for preparing a lithium iron phosphate cathode material includes the following steps: (1) Anhydrous iron phosphate and lithium carbonate (first lithium source) were mixed at a molar ratio of Li to Fe of 0.75:1, and glucose (carbon source) was added. The amount of glucose added was 10% of the mass of anhydrous iron phosphate. The mixture was placed in a sintering furnace under nitrogen atmosphere protection and pre-lithiation was carried out at a temperature of 420°C for 5 hours to obtain the pre-lithiation product. (2) The pre-lithiation product is mixed and dispersed with lithium carbonate (second lithium source) and titanium dioxide (dopant) in deionized water. The amount of the second lithium source added is such that the total molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is 1.02:1, and the amount of titanium dioxide added is 0.8% of the mass of anhydrous iron phosphate, to prepare a slurry with a solid content of 55wt%. (3) The slurry is put into a sand mill for grinding until the D50 of the slurry reaches 0.7μm, and then spray-dried (inlet air temperature 250℃, outlet air temperature 100℃) to obtain precursor powder. (4) The precursor powder was placed in a sintering furnace under nitrogen atmosphere protection and sintered at 760°C for 8 hours. (5) The sintered material is subjected to air jet pulverization, sieve through 300 mesh, and demagnetization treatment to obtain lithium iron phosphate cathode material.
[0035] The difference between this comparative example and Example 1 is that the carbon source is added during the pre-lithiation treatment in step (1), instead of being added together with the second lithium source in step (2). The rest is the same as Example 1.
[0036] Performance testing The performance of the lithium iron phosphate cathode materials prepared in the examples and comparative examples was tested, and the test process is as follows: (1) Powder conductivity test: According to GB / T 30835-2014 "Carbon composite lithium iron phosphate cathode material for lithium-ion batteries", a four-probe tester was used for testing.
[0037] (2) Powder compaction density test: The test was conducted in accordance with GB / T 44330-2024 "Determination of compaction density of lithium-ion battery cathode material powder".
[0038] (3) Particle size distribution test: The median particle size D50 of the material was determined using a laser particle size analyzer.
[0039] (4) Electrochemical performance testing: The lithium iron phosphate cathode material prepared in the examples and comparative examples was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 90:5:5. N-methylpyrrolidone was added and ground into a uniform slurry, which was then coated onto aluminum foil. After vacuum drying at 120°C for 12 hours, the slurry was cut into cathode sheets with a diameter of 14 mm. Using lithium metal sheets as the anode and polypropylene microporous membranes as the separator, and 1 mol / L LiPF6 dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1) as the electrolyte, CR2032 coin cells were assembled in an argon-filled glove box and electrochemical performance testing was performed.
[0040] Charge-discharge tests were conducted on the Blue Battery testing system, with a voltage range of 2.0~3.75V and a test temperature of 25℃. The first charge-discharge test was performed at a 0.1C rate, recording the initial charge specific capacity and initial discharge specific capacity, and calculating the initial coulombic efficiency: Initial coulombic efficiency (%) = (Initial discharge specific capacity / Initial charge specific capacity) × 100%. Constant current charge-discharge tests were then performed at 0.1C and 1C rates, recording the discharge specific capacity at each rate. Cycle performance testing was conducted at a 1C rate, recording the capacity retention rate after 500 cycles.
[0041] Table 1 Performance test results of the examples and comparative examples
[0042] As shown in Table 1, in Examples 1 to 3, by controlling the amount of the first lithium source added in the pre-lithiation stage, the pre-lithiation temperature, and the subsequent sintering temperature, the obtained lithium iron phosphate cathode materials all exhibited excellent comprehensive performance, with conductivity, compaction density, discharge specific capacity, and cycle capacity retention all significantly better than those of the comparative examples.
[0043] Comparing Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 did not undergo pre-lithiation treatment. Instead, it directly mixed anhydrous iron phosphate with all lithium sources, carbon sources, and dopants and then sintered in one step. Its conductivity, compaction density, 1C discharge specific capacity, and cycle capacity retention were all significantly lower than those of Example 1. This indicates that without pre-lithiation treatment, the reactivity of iron phosphate and lithium sources during the sintering process is insufficient, and the grains are prone to abnormal growth, resulting in uneven particle distribution and an inability to form a dense particle packing structure. The compaction density and electrochemical performance of the material are significantly degraded.
[0044] Comparing Example 1 with Comparative Examples 2 and 3, it can be seen that the amount of the first lithium source added in the pre-lithiation stage has a significant impact on the product performance. In Comparative Example 2, the pre-lithiation Li to Fe molar ratio is too low, and the lithium source is insufficient to fully activate the lattice of iron phosphate, resulting in insufficient intermediate phase formation and failing to effectively improve the subsequent sintering reaction. In Comparative Example 3, the pre-lithiation Li to Fe molar ratio is too high, and excessive lithium source in the pre-lithiation stage easily leads to the formation of local lithium-rich phases, which is also not conducive to the uniformity of the subsequent lithiation reaction. The compaction density, conductivity, and cycle capacity retention of both examples are significantly lower than those of Example 1, indicating that both excessively low and excessively high pre-lithiation Li to Fe molar ratios are not conducive to obtaining high-performance lithium iron phosphate products.
[0045] Comparing Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 increased the pre-lithiation temperature to 600°C. At this temperature, the grain size and composition of the pre-lithiation product changed, the intermediate phase composition became more complex, and its various performance indicators were lower than those of Example 1, indicating that excessively high pre-lithiation temperature would lead to a more complex intermediate phase composition.
[0046] Comparing Example 1 and Comparative Example 5, it can be seen that when the sintering temperature of Comparative Example 5 is increased to 900°C, the primary particles undergo over-sintering and abnormal growth (D50 reaches 1.18 μm) at this excessively high temperature. The porosity between particles increases, which destroys the particle packing structure. As a result, the compaction density, electrical conductivity and cycle capacity retention are significantly lower than those of Example 1. This shows that excessively high sintering temperature is not conducive to improving the material properties.
[0047] Comparing Example 1 and Comparative Example 6, it can be seen that in Comparative Example 6, the carbon source was added during the pre-lithiation stage. The carbon source partially pyrolyzed at the pre-lithiation temperature, which interfered with the normal progress of the pre-lithiation reaction and changed the formation environment of the pre-lithiation product. This affected the lattice activation effect, and the compaction density and electrochemical performance of the product were lower than those of Example 1. This indicates that the carbon source should be added together with the second lithium source after the pre-lithiation is completed to ensure that the formation environment of the intermediate phase is not disturbed.
[0048] The above results show that by controlling the amount of the first lithium source added in the pre-lithiation stage, the pre-lithiation temperature, the order of carbon source addition, and the sintering temperature, the present invention can effectively activate the crystal structure of anhydrous iron phosphate, increase the reactive sites, promote the uniform precipitation and growth of lithium iron phosphate grains, and make the particle distribution of the product more concentrated and the crystal phase more pure, thereby achieving the improvement of high compaction density, high conductivity, high discharge specific capacity and excellent cycle stability.
[0049] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a lithium iron phosphate cathode material, characterized in that, Includes the following steps: (1) Anhydrous iron phosphate is mixed with the first lithium source and pre-lithiation is carried out at 430~530℃ under an inert atmosphere to obtain the pre-lithiation product; (2) The pre-lithiation product, the second lithium source, the carbon source, and the dopant are added to a solvent and mixed and dispersed to obtain a slurry; (3) Grind the slurry and spray dry it to obtain precursor powder; (4) The precursor powder is sintered at 720~800℃ under an inert atmosphere; (5) The sintered product is crushed, sieved and demagnetized to obtain lithium iron phosphate cathode material.
2. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the first lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; the molar ratio of iron in anhydrous iron phosphate to lithium in the first lithium source is 1:(0.60~0.85); and the pre-lithiation treatment time is 2~8h.
3. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the second lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium oxalate; the amount of the second lithium source added is such that the molar ratio of lithium element in the slurry to iron element in anhydrous iron phosphate is (1.00~1.05):
1.
4. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the carbon source is selected from at least one of glucose, sucrose, starch, citric acid, polyethylene glycol, and polyvinyl alcohol; the amount of carbon source added is 5 to 18% of the mass of anhydrous ferric phosphate.
5. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the dopant is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium tetrachloride, ammonium metavanadate, and magnesium oxide; the amount of dopant added is 0.05 to 1.5% of the mass of the anhydrous iron phosphate.
6. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, The solid content of the slurry in step (2) is 40~70wt%.
7. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, The sintering time in step (4) is 4~12h.
8. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that, In steps (1) and (4), the inert atmosphere is nitrogen or argon.
9. A lithium iron phosphate cathode material, characterized in that, The lithium iron phosphate cathode material was prepared by the method described in any one of claims 1-8.
10. The application of the lithium iron phosphate cathode material as described in claim 9 in lithium batteries.
